Being there from afar: The media event relocated to the public viewing area. Issue 2 (1st June 2014) - Becker, Karin; Widholm, Andreas
This article examines the media event as relocated to public viewing areas (PVAs) erected in cities across the globe, where people gather to watch the events together live on-screen. The study is based on ethnographic research carried out in PVAs located in selected cities during the 2010 FIFA World Cup and the 2012 Summer Olympics. We examine the relationships between these events, as reconstituted in these different locations through media networks, and the public's participation via the event on-screen. The PVA emerges as a new location of experience and participation, with its own histories as a place of attraction for the local public and for visitors from afar, in what D. Massey would describe as an 'intersection of local and global social relations'. The host city arena is no longer the self-evident 'centre' for this event, which has been pluralized through the complex web of media structures and the activities of participants who come to experience the event in these other, dispersed locations.